Caracterização temporal da temperatura do ar e sua relação com os elementos climáticos e eventos Enos na cidade de Boa Vista - RR - Silva, Danielle Alves da (2018)
The State of Roraima presents diverse physiographic characteristics standing out within the immense Amazon region of our country. Much of this diversity is conditioned by the climatology existing in the State. Since climate is one of the determining factors for the formation and transformation of the landscape, for the development of agriculture and for the numerous economic and social activities, studying the meteorological time series of Boa Vista has shown to be relevant, since it allows a broader view of the changes that occurred over time. In this way, this research has the objective to analyze comparatively the temperature and the climatic elements, as well as the influence of the ENSO phenomena on the thermics of the city of Boa Vista - RR in the period from 1944 to 2016, seeking to identify the degree of interference of such elements /phenomena on the climatic dynamism of the city. In order to reach this objective, statistical methods of monthly averages, annual averages, standard deviation, variance, and determination index were used to identify the average temperature variation. As a result, the average temperature was constant during the series and, before the 1990s, the average annual values were below the historical average (28.4 ° C). Autumn is the hottest period of the year, during which time high temperatures persist during the Winter (December to February), with average temperatures of 28 ° C to 29 ° C. These high temperatures are only alleviated in Spring and Summer with the elevation of precipitation rates, cloud cover and, consequently, the URA index, during this period the average temperature reaches 26.9 ° C, that is, an average reduction of 2.1 ° C. The El Niño periods have a higher impact on the temperatures of the city of Boa Vista with changes that can reach a 5.3% average increase when analyzed in periods of very strong intensity. In La Niña periods, the effects are lower, causing a reduction in temperature at the rate of 0.7% only when analyzed in periods of low and moderate intensity. In periods of strong intensity, the degree of influence is zero, since the average of its values equals the annual average of 28.4 ° C. Therefore, with the results found, it is expected to contribute to the understanding and research concerning the climatic dynamics of the city of Boa Vista and the State of Roraima.